Бумажные книги Лали: повесть-сказка / Федор Кнорре - Кнорре Федор Федорович (Любимое чтение, 2006)
Экземпляры: ф.13 (2006) / Инвентарный номер: 50326 / Цена: / Сис.шифр: 84(2Рос=Рус)6-4 / Авт.знак: К 53 / ГРНТИ: 17.82.93 / ББК: 84(2Рос=Рус)6-44